Theranostics: Polymer‐Coated Radioluminescent Nanoparticles for Quantitative Imaging of Drug Delivery (Adv. Funct. Mater. 37/2014). (October 2014) - Moore, Thomas L.; Wang, Fenglin; Chen, Hongyu; Grimes, Stuart W.; Anker, Jeffrey N.; Alexis, Frank
<x xml:space="preserve">Abstract</x> F. Alexis and co‐workers use X‐ray excited optical luminescent nanoparticles (XEOL NPs) to quantitatively measure intracellular drug release. On page 5815, XEOL NPs or radioluminescent NPs, are loaded with the photoactive drug protoporphyrin IX (PpIX). The overlap between the XEOL NP emission and the PpIX absorption enables a quantitative approach to measure drug loading and release kinetics in both buffer solution and into cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>